Expression patterns of genes in steroidogenic, cholesterol uptake, and liver x receptor-mediated cholesterol efflux pathway regulating cholesterol homeostasis in natural and PGF2α induced luteolysis as well as early pregnancy in ovine corpus luteum - Hitit, Mustafa; Kose, Mehmet; Kocak, Nadir; Atli, Mehmet Osman (Elsevier BV, 2022)
The aim was to evaluate the expression of genes of steroidogenic, cholesterol uptake, and liver X receptor (LXR) mediated cholesterol efflux pathway in ovine corpus luteum (CL) during natural and prostaglandin F2α (PGF2α) induced luteolysis and early pregnancy. For this study, two experiments were carried out 1); ewes were grouped into two sub-groups as cyclic 12 (C12, n = 4) and 16 (C16, n = 4) and pregnant 12 (P12, n = 4), 16 (P16, n = 4), and 22 (P22, n = 4). Additionally, 2) ewes were grouped into four groups following treatment of PGF2α, the duration of PGF2α challenge at 1 (PG1, n = 4), 4 (PG4, n = 4), and 16 (PG16, n = 4) hours on day 12 of the cycle was compared with 0 h. The corpus luteum tissue samples were collected on the corresponding estrus cycle and pregnancy days, and RNA was extracted using Trizol. mRNA expression levels of the steroidogenic (StAR, CYP11A1, and HSD3B1) and cholesterol uptake receptors (SCARB1 and LDLR) and LXR pathway (NR1H3, NR1H2, ABCA1, and ABCG1) were assessed using quantitative PCR (qPCR), and protein of LXR pathway was investigated using western blot. In-situ hybridization was used to detect mRNA localization. Steroidogenic and cholesterol uptake mRNAs were decreased in C16, while NR1H2 and ABCG1 were increased in C16, compared to C12. Steroidogenic and cholesterol uptake mRNA was greater in P16 than in C16. NR1H2 and ABCA1 protein expression were higher in P16 than in C16. LDLR mRNA was higher in P22 than in P12, while SCARB1 was higher in P16 than in P12. NR1H2 mRNA was greater in P22 than in P12. Steroidogenic and cholesterol uptake mRNA were decreased in PGF2α-induced luteolysis groups against C12. ABCG1 mRNA was higher in PG16 than in PG4 and PG1. The reduction of lipoprotein receptors rather than LXR-mediated reverse transport may contribute to the decline in progesterone (P4) in natural and functional luteolysis.
Keywords: Sheep; Luteolysis; Early Pregnancy; Dinoprost; Ovine; Liver X Receptor; Cholesterol; Corpus Luteum; Pregnancy; Animals; Homeostasis; Female; RNA, Messenger; Progesterone; Sheep, Domestic; Liver X Receptors; 3. Good health